(untitled) (Texas Journal of Medical Science, 2022)
Hypertrophic cardiomyopathy (GKM), according to the current classification [1], is classified as primary cardiomyopathies, primarily a genetically determined disease of the heart muscle characterized by a complex set of specific morphofunctional changes and a steadily worsening course. The symptoms of the disease are varied and vague and are associated with hemodynamic disturbances - diastolic dysfunction against the background of massive hypertrophy of the left (CH Q) and or right ventricular myocardium, often asymmetric due to thickening of the interventricular septum (IVS), left ventricle (CH Q) with frequent development of outflow tract obstruction, myocardial ischemia, pathology of autonomic circulation regulation and disruption of electrophysiological processes in the heart [2-4]. The prognosis in GCM is variable, so one of the main challenges is to differentiate the risk of fatal complications of the disease, to look for available prognostic prognosis and criteria for evaluating the effectiveness of treatment [5]. Currently, the possibility of determining the level of circulating natriuretic peptides (NUP) as a biochemical sign of the severity of myocardial dysfunction and prognosis in patients with cardiovascular pathology is widely discussed. High levels of NUP in blood plasma have been shown to be an early and sensitive sign of CH Q dysfunction, associated with heart failure severity (HF) [6 - 8], as well as an increased risk of cardiovascular complications and death. In patients with HF and acute coronary syndrome [9-11]. Patients with HKM were also found to have increased NUP levels, possibly due to myocardial hypertrophy, increased CH Q filling pressure, and CH Q obstruction [12, 13]. However, the contribution of each of these components to the genesis of increased peptide secretion is unclear, and further studies are needed to compare the characteristics of clinical hemodynamic status and NUP levels in patients with HCM. The aim of this study was to comprehensively study the main clinical and hemodynamic parameters and NUP levels in the blood plasma of patients with GKM